A rhomboid-shaped printed monopole antenna for wideband circular polarization - Lwin Zaw Myo (Faculty of Technical Sciences in Cacak, 2021)
This paper presents the design of a wideband circularly-polarized printed monopole antenna with a rhomboid shape. The rhomboid-shaped patch is fed by a microstrip line offset from the center to generate circular polarization (CP). The ground plane configuration is optimized for wide bandwidth operation. Bandwidth (satisfying both 10-dB return loss and 3-dB axial ratio) of 76% (1.92 - 4.27 GHz) is achieved in this research. The size of the proposed antenna is 0.386 2 0 l (55×66 mm2) where λ0 is the free space wavelength which corresponds to the center frequency of the bandwidth. The antenna has a fractional bandwidth-size ratio (BW/size) of 1.97 which is higher than most CP monopole antennas in the literature. This antenna is suitable for Wi-Fi, WiMAX, and other wireless applications which outperform using circular polarization.